Pulmonary infection with Aeromonas dhakensis in a patient with acute T lymphoblastic leukemia: a case report and review of the literature - Wang, Chaoyang; Wei, Nan; Zhang, Moyuan; Zhang, Xiaoju (Frontiers in Medicine, 2024)
Background Aeromonas dhakensis is a gram-negative bacterium. In recent years, Aeromonas dhakensis has gradually attracted increasing attention due to its strong virulence and poor prognosis. Clinical reports of pulmonary infection caused by Aeromonas dhakensis are rare. Case presentation A patient with acute T lymphoblastic leukemia experienced myelosuppression after chemotherapy, developed a secondary pulmonary infection with Aeromonas dhakensis and was hospitalized due to fever. The patient underwent testing for inflammatory markers, chest imaging, blood culture, bronchoalveolar lavage, pleural drainage, and metagenomic next-generation sequencing of alveolar lavage fluid and pleural fluid to obtain evidence of Aeromonas dhakensis infection, and was treated with four generations of cephalosporin combined with fluoroquinolone antibiotics. The patient’s condition significantly improved. Discussion Among pulmonary infectious pathogens, Aeromonas dhakensis is relatively rare. Once an Aeromonas strain is cultured in the clinical work, pathogenic sequencing should be performed on the detected samples for early accurate diagnosis and effective anti-infection treatment.